2016
DOI: 10.1007/s00213-016-4385-8
|View full text |Cite
|
Sign up to set email alerts
|

The nociceptin/orphanin FQ receptor agonist SR-8993 as a candidate therapeutic for alcohol use disorders: validation in rat models

Abstract: RationaleAlcoholism is a complex disorder in which diverse pathophysiological processes contribute to initiation and progression, resulting in a high degree of heterogeneity among patients. Few pharmacotherapies are presently available, and patient responses to these are variable. The nociceptin/orphanin FQ (NOP) receptor has been suggested to play a role both in alcohol reward and in negatively reinforced alcohol seeking. Previous studies have shown that NOP-receptor activation reduces alcohol intake in genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 56 publications
2
15
0
2
Order By: Relevance
“…For example, infusion of nociceptin into brain ventricles reduced alcohol conditioned reward as well as relapse-like behavior provoked by either stress or alcohol-related cues (Ciccocioppo et al, 2004; Martin-Fardon et al, 2000). Likewise, systemic administration of brain-penetrant nociception analogues reduced alcohol self-administration (Aziz et al, 2016; Ciccocioppo et al, 2014; Kuzmin et al, 2007). Direct injection of nociceptin into the CeA also was reported to reduce alcohol consumption (Economidou et al, 2008).…”
Section: Mechanisms Underlying Chronic Alcohol Stress and Drinkimentioning
confidence: 99%
See 1 more Smart Citation
“…For example, infusion of nociceptin into brain ventricles reduced alcohol conditioned reward as well as relapse-like behavior provoked by either stress or alcohol-related cues (Ciccocioppo et al, 2004; Martin-Fardon et al, 2000). Likewise, systemic administration of brain-penetrant nociception analogues reduced alcohol self-administration (Aziz et al, 2016; Ciccocioppo et al, 2014; Kuzmin et al, 2007). Direct injection of nociceptin into the CeA also was reported to reduce alcohol consumption (Economidou et al, 2008).…”
Section: Mechanisms Underlying Chronic Alcohol Stress and Drinkimentioning
confidence: 99%
“…This effect may be mediated by nociception interacting with alcohol-induced modulation of GABA and glutamate transmission in the CeA (Kallupi et al, 2014a; Kallupi et al, 2014b). Additionally, chronic alcohol exposure appears to enhance sensitivity to NOP activation, as nociceptin (or its analogues) were shown to be more effective as anxiolytics and reducing elevated drinking associated with dependence (Aujla et al, 2013; Aziz et al, 2016; de Guglielmo et al, 2015; Economidou et al, 2011; Martin-Fardon et al, 2010). …”
Section: Mechanisms Underlying Chronic Alcohol Stress and Drinkimentioning
confidence: 99%
“…Beyond their role in analgesia, in part because the NOP peptide can inhibit the beta-endorphin neurons that may mediate alcohol abuse [64,65], NOP receptors have been investigated in rodent models of AUD. These studies have consistently demonstrated that stimulating NOP receptors can decrease the abuse-related effects of ethanol [22][23][24][25][26][27][28][29][30]. The present studies compared the effects of the MOP receptor agonist buprenorphine and the bifunctional MOP/NOP agonist BU08028 in rhesus monkeys who had free access to a 4% ethanol solution 6 h per day, 5 days per week.…”
Section: Discussionmentioning
confidence: 90%
“…For example, NOP receptor agonists can decrease neurochemical and neurophysiological effects of ethanol in rats [20,21]. Moreover, administration of the NOP peptide or NOP receptor agonists can attenuate behavioral effects of ethanol in rodent models, including ethanol self-administration, ethanol seeking, and symptoms of ethanol withdrawal [22][23][24][25][26][27][28][29][30]. More recently, it was reported that antagonism or genetic deletion of NOP receptors also decreased ethanol drinking [31,32], and that a NOP receptor antagonist reduced heavy drinking in a clinical trial [33].…”
Section: Introductionmentioning
confidence: 99%
“…The latter findings suggest a history of alcohol dependence dysregulates the nociceptin system, which can be reversed with NOP agonist treatment. A different small-molecule NOP agonist, SR-8993, blocked YOH-reinstatement of alcohol seeking ( Aziz et al, 2016 ). Conversely, other studies have found that NOP antagonists and NOP knockout mice produce anti-obesity and anti-depressant effects (review by Witkin et al, 2014 ), and the orally bioavailable, brain-penetrant, NOP antagonist LY2940094 blocked YOH-reinstatement of alcohol seeking in alcohol-preferring rats ( Rorick-Kehn et al, 2016 ).…”
Section: Neuropharmacological Targetsmentioning
confidence: 99%